Varicella Zoster Virus Cerebellitis Without a Rash in an Immunocompetent 85-Year-Old Patient. Issue 3 (September 2015) - Shilo, Smadar; Wiener-Well, Yonit; Korn-Lubetzki, Isabelle
<x xml:space="preserve">Abstract</x> Background: Reactivation of the varicella zoster virus (VZV) in adults rarely presents with neurological symptoms without a rash. To our knowledge, so far, only 3 additional cases of VZV cerebellitis, which presented without a rash and were proven by cerebrospinal fluid analysis, have been reported in the literature. Case Report: An immunocompetent 85-year-old patient presented with a new-onset tremor. He had no rash, had a normal brain computed tomography and magnetic resonance imaging, and had minimal cerebrospinal fluid findings. Eventually, he was diagnosed as having varicella zoster virus cerebellitis only on the basis of a virological examination. Conclusions: The manifestation of a new-onset tremor and gait ataxia should raise a suspicion of cerebellitis caused by VZV, even in the absence of cutaneous manifestations or typical imaging findings.